DESIGNING AN E-DOCUMENT EMPLOYMENT INFORMATION SYSTEM AT THE OFFICE OF BALAI BESAR WILAYAH SUNGAI MESUJI SEKAMPUNG - Brilliant, Muhammad; Rifa'i, Rendra Nasrul; Anggraeni, Mareta (Asia Information System Journal, 2022)
Currently the management of employee data, performance appraisal, and incoming and outgoing mail is a routine activity carried out by the Head of Subsection of the Balai Besar Wilayah Sungai Mesuji Sekampung (BBWSMS). Document management is still using Microsoft Office and must be printed first if the document is to be submitted to other employees so that apart from the slow process of sending documents, of course, document files that are piling up are unavoidable. The system development method used in this research is the Structured Systems Analysis and Design (SSAD) methodology. This methodology has several important steps that must be carried out in designing and building e-documents at the BBWSMS Center. a better and maximum work process is produced by using a centralized data storage in a database that can facilitate data addition, search, and publication of data using computer technology. The E-document application would be better if it was developed to be based on Android or mobile so that it can be easily accessed. through mobile devices for all employees at BBWSMS